Evaluation of a stabilized sand residue for use as roadway materials - Jitsangiam, Peerapong; Nikraz, Hamid; Siripun, K. (Southeast Asian Geotechnical Society, 2009)
Australia produces approximately 40% of the world’s bauxite and over 30% of the world’s alumina. Each year, about 25 million tons of sand residues are produced in Australia. The management and containment of large impoundment areas are costly. The sustainable use of coarse sand residues for road construction is an attractive option with a high potential for large volume reuse. During the extraction of alumina from bauxite ore using the Bayer process, a fine residue is produced called red mud. In Western Australia, Darling Range bauxite deposits contain high levels of quartz, which results in a coarse residue fraction also being produced. This study focuses on whether a coarse sand residue is a viable option for use as a road base material in Western Australia. The soil stabilization technique, a pozzolanic- stabilized mixture, was used to improve the properties of a coarse sand residue to satisfy minimum requirements of road bases. The intent of this stabilization technique is to use potential by-products from industry in Western Australia as stabilizing materials. A pozzolanic - stabilized mixture consisting of Class F fly ash, a by-product from a coal power station, and activators, the by-product from the quicklime manufacturing in terms of lime kiln dust, were employed to develop pozzolanic activity.Once the appropriate mixture of a coarse sand residue, fly ash, and activators was established (based on a maximum dry density and a value of unconfined compressive strength), a set of laboratory tests were performed. These included an unconfined compressive strength test, a resilient modulus test, and a permanent deformation test. Comparisons were made between the stabilized residue and the conventional road base material in West Australia (crushed rock with the addition of 2% General Purpose (GP) Portland Cement.). The results of this study show that the performance of the stabilized residue is superior to that of the standard use material. Our findings indicate that stabilized residue can provide improved performance when used as road base material in Western Australia.